Study on Implementation of Activity-Based Costing (ABC) System on Determination of Indirect Costs in Ship Production - Wahidi, Sufian Imam; Virmansyah, Vialdo Muhammad; Pribadi, Triwilaswandio Wuruk (Department of Naval Architecture - Diponegoro University, 2021)
Currently, business development, especially in the maritime sector, has quite rapid progress in Indonesia. Recently, the shipbuilding industry's development is an effort to improve competitiveness with the global market. With the increasing development of the shipbuilding industry in Indonesia, cost accounting as a cost information system is challenged to develop the shipbuilding industry, requiring high product quality. This matter requires the company to decide on proper budget planning not to experience losses. Activity-Based Costing (ABC) System is a system to determine costs using activities to classify costs to produce indirect costs that are more systematic and relevant. Activity-based costing systems identify resources in each department's activities to provide information about a product's cost. It collects indirect costs and allocates them to various products in proportion to the product volume. Therefore, activity-based costing can estimate the product costs and individual activity costs used in the production well. The first step is classifying activities, associating various costs with various activities, determining homogeneous cost groups, and determining group rates. The second step of this stage is the determination of overhead prices selected from each cost group. This research compares indirect costs to the construction of 2x1800 HP tugboat ships according to traditional cost accounting methods with the Activity-Based Costing System method. The first method's result is 3,432,920,043 IDR and the second method is 2,231,760,472 IDR.